Comparative Transcriptomics Unravels Prodigiosin's Potential Cancer-Specific Activity Between Human Small Airway Epithelial Cells and Lung Adenocarcinoma Cells - Davient, Bala; Ng, Jessica Pei Zhen; Xiao, Qiang; Li, Liang; Yang, Liang (Frontiers in Oncology, 2018)
Objective: Non-Small Cell Lung Cancer (NSCLC) is extremely lethal upon metastasis and requires safe and effective systemic therapies to improve a patient's prognosis. Prodigiosin (PG) appears to selectively and effectively target cancer but not healthy cells. However, PG's cancer-specific activity has remained elusive until recently. Methods: PG's cancer-specific performance was compared to Docetaxel (DTX), Paclitaxel (PTX), and Doxorubicin (DOX) against human lung adenocarcinoma (A549) and human small airway epithelial cells (HSAEC). Combination of PG with DTX, PTX, or DOX in a 1:1 ED50 ratio was also evaluated. MTT assay was used to determine the post-treatment cell viability. RNA-sequencing was used for comparative transcriptomics analysis between A549 and HSAEC treated with 1.0 μM PG for 24 h. Results: PG reduced A549 cell viability by four-folds greater than HSAEC. In comparison to DTX, PTX and DOX, PG was ~1.7 times more toxic toward A549, and 2.5 times more protective toward HSAEC. Combination of PG in a 1:1 ED50 ratio with DTX, PTX, or DOX failed to exhibit synergistic toxicity toward A549 or protection toward HSAEC. In A549, genes associated in DNA replication were downregulated, while genes directly or indirectly associated in lipid and cholesterol biogenesis were upregulated. In HSAEC, co-upregulation of oncogenic and tumor-suppressive genes was observed. Conclusion: An overactive lipid and cholesterol biogenesis could have caused A549's autophagy, while a balancing-act between genes of oncogenic and tumor-suppressive nature could have conferred HSAEC heightened survival. Overall, PG appears to be a smart chemotherapeutic agent that may be both safe and effective for NSCLC patients.